Exploring the Mediating Role of User Engagement in the Relationship Between Immersive Experiences and User Satisfaction in Virtual Reality Gaming - Hammami, Hanene (International Review of Management and Marketing, 2024)
This study aims to investigate the influence of virtual reality (VR) on immersive experiences, user satisfaction, and engagement, focusing on the emotional and cognitive dimensions that enhance the overall gaming experience. Conducted at VR Land Carthage in Tunisia (https://tunis.carthageland. com/fr/vr-land/), a platform offering immersive VR gaming, the research utilized both online and offline surveys, yielding 254 valid responses. Data were analyzed using Smart Partial Least Squares (PLS) 3, facilitating a comprehensive examination of the relationships among immersive experiences, user engagement, and satisfaction in VR gaming. The findings indicate a strong positive relationship between immersive VR experiences and user satisfaction, with user engagement acting as a mediator. Immersion significantly enhances the gaming experience; players emotionally connected to the game report higher satisfaction and increased likelihood of return. The study highlights the importance of interactive elements in fostering deep engagement. Limitations include a sample size constrained by time and accessibility, potentially affecting the generalizability of the findings beyond the Tunisian context. Practically, the research underscores the need for developers to enhance immersion through interactive features, such as social connectivity and adaptive storytelling, to boost player involvement and satisfaction, ultimately contributing to retention and success in the competitive VR gaming market. This research addresses a gap in empirical studies on user engagement and satisfaction in specific gaming environments, offering valuable insights for developers and researchers in understanding how immersive experiences drive engagement in VR gaming.